Spatial analysis of morphological variation in African honeybees (Apis mellifera L.) on a continental scale - (:unkn) unknown (My University, 2000)
Population differentiation of African honeybees has been analysed in a spatial context encompassing the continent's wide geographical range and environmental heterogeneity, based on 10 morphological characters measured from 268 local populations. While autocorrelation indicates a continuous large-scale decrease in similarity in general, clustering of single character correlograms suggests four distinct groups of profiles. This pattern, further supported by mapping factor scores, canonical trend surface analysis axes scores, suggests a variety of microevolutionary mechanisms acting at distinct scales in time and space in different groups of characters. Association with large-scale differences in vegetation, climate and traditional subspecific classification has been analysed by analysis of variance (ANOVA). The most important aspect is that the results support the hypothesis that traditional subspecies, at least as defined by these characters, seem to represent integrated evolutionary units well adapted to their local conditions.
Keywords: African Research